THE IMPACT OF SUSTAINABILITY REPORTING ON COMPANY PERFORMANCE - Annisa Hayatun N. Burhan; Wiwin Rahmanti (Journal of Economics, Business, and Accountancy Ventura, 2012)
Sustainability reporting and company performance are the two factors that need to be studiedin recent years. Sustainability Reporting is non-financial report that consists of three elementswhich are economic performance, environmental performance, and social performance.This research attempts to examine the relationship between sustainability reporting asa whole and each of the elements of sustainability reporting with company performance. Itconsists of 32 companies listed on Indonesian stock exchange during the period of year 2006-2009. The independent variables are sustainability reporting, economic performance disclosure,environmental performance disclosure, and social performance disclosure. These variablesare measured by means of disclosure index. Sustainability Reporting Guidelines fromGlobal Reporting Initiative (GRI) is used as the basis of calculating the index score. The dependentvariable is Return on Asset (ROA) as a measure of economic performance. This researchuses secondary data collected from company website and Indonesian stock exchange.The result shows that sustainability reporting influences company performance. However,partially, only social performance disclosure influences the company performance.